Hubungan antara Indeks Produksi Retikulosit (IPR) dengan Red Blood Cell Distribution Width (RDW) pada Klasifikasi Anemia berdasarkan Defek Fungsional - Setyawati, Setyawati; Pembantjanawati, Endah; Rosita, Linda (Lembaga Penelitian Universitas YARSI, 2008)
Reticulocyte Production Index (RPI) is a shift correction for the presence of reticulocyte that can assesses the real erythropoietic response of the bone marrow. RPI can be used to classify anemia as result from functional defect, i.e. RPI<2 for hypoproliferative and maturation defect anemia, and RPI>3 for hemolytic anemia. Measurement of Red Blood Cell Distribution Width (RDW) is the mathematical representation of variance within the size distribution of the red cell population. The objective of this study was to identify the variation of the red cell size within the population measured (anisocytosis) enable to determine the cell population as homogeneous (normal RDW) or heterogenous (increased or high RDW). The role of RDW to differentiate functional defect anemia with RPI<2 has not been studied. This study was done at Hematology Department Dr. Sardjito Hospital. In such a cross sectional study, the subjects were considered as anemic patients based on automated laboratory analyzer, peripheral blood smear, and reticulocyte count result. The result showed that seventy patients met the inclusion criteria. Sixty seven patients (95,71%) had RPI<2 classified as hypoproliferative and maturation defect anemia, 2 patients (2,85%) had RPI = 2-3 classified as borderline group and 1 patient (1,42%) had RPI>3 classified as hemolytic anemia. Means for reticulocyte count, corrected reticulocyte count, RPI, and RDW for hypoproliferative and maturation defect anemia were 2,8% and 2,3%; 1,1% and 1,1%; 0,4 and 0,5; 21,8% and 17,8% respectively, with p value by the Wilcoxon Signed Ranks Test are = 0,322; 0,52; 0,273; and 0,27 (CI = 95%). The proportion of anisocytosis and normocytosis for hypoproliferative anemia were 76,08% and 23,9% and for maturation defect anemia were 76,19% and 23,8% with Chi-Square test 0,000 and p = 0,993. No correlation between was observed RDW and RPI<2 with Spearman correlation (r = 0,0297 and p = 0,993). It is concluded that the use of RDW and RPI is not always useful to differentiate hypoproliferative and maturation defect anemia on the group of anemia categorized as RPI<2 without support from another laboratory test especially in combined anemia.